Large aneurysm of left coronary sinus of Valsalva presenting with effort-related ventricular fibrillation - Falconieri, Fabio (Oxford University Press, 2013)
Sinus of Valsalva aneurysms are very rare and are often asymptomatic. Clinical manifestations depend on associated complications, most commonly rupture or dissection. We describe the unusual case of a 46-year old presenting with exercise-induced ventricular fibrillation due to extrinsic compression of the left coronary artery. We also describe the surgical correction by valve-sparing aortic root replacement.